2022
DOI: 10.3389/fphar.2022.1018394
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Application of non-VKA oral anticoagulants in patient of idiopathic hypereosinophilic syndrome with intracardiac thrombus

Abstract: Idiopathic hypereosinophilic syndrome (IHES) is a rare but life-threatening disease related to a group of myeloproliferative disorders characterized by prolonged eosinophilia of unknown cause and inflammatory damage to multiple organs. Here, we present a 44-year-old female patient complaining of shortness of breath and palpitations for 1 month. Her history and presentation were unremarkable, except for a 3-years history of rheumatoid arthritis treated with ibuprofen (0.3 g per day). Initial examination showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Early data have suggested that the risk for thrombotic events remains elevated even after normalization of the eosinophil count, suggesting that the degree of disease activity is an important risk factor [ 10 ]. Finally, although vitamin K antagonists are most commonly used for intracardiac thrombus, reports have suggested that direct oral anticoagulants may be safely used as an alternative [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early data have suggested that the risk for thrombotic events remains elevated even after normalization of the eosinophil count, suggesting that the degree of disease activity is an important risk factor [ 10 ]. Finally, although vitamin K antagonists are most commonly used for intracardiac thrombus, reports have suggested that direct oral anticoagulants may be safely used as an alternative [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A possible reason why the external application of mirabilite is effective for postpartum milk return is that its main component can absorb the surrounding water with the help of osmotic pressure in a hypertonic environment (Shen, 1997). In addition, the salty taste of mirabilite softens the breasts, and its cold character lowers the temperature of the skin, normalizes the body temperature, opens the mammary ducts, and promotes the discharge of milk, which plays a role in the return of milk (Zou and Li, 2008). Li et al (2022) applied mirabilite and raw R. palmatum to prevent breast accumulation in parturient.…”
Section: Breast Accumulation Breast Distention Mastitismentioning
confidence: 99%